Is new variant Chlamydia trachomatis present in England and Wales?. Issue 1 (12th September 2007) - Alexander, S; Ison, C
Abstract : Background: A new variant C trachomatis (nvCT) strain has been recently isolated in Sweden, which has a 377 bp deletion in a portion of the plasmid that is the target area for some C trachomatis nucleic acid amplification tests (NAATs). Consequently, these platforms generate false negative results when presented with this strain. Objective: To determine if nvCT is present in England and Wales. Methods: Specimens which had been determined to be C trachomatis positive using an unaffected platform were tested for the presence of the deletion using an in-house nested PCR assay which generated a 253 bp fragment in new variant strains and a 630 bp fragment in wild-type strains. The specimens tested could be divided into two main groups: ( a ) 933 specimens sourced from patients attending both genitourinary medicine services and the National Chlamydia Screening Programme were forwarded from eight key laboratories within England and Wales; ( b ) 179 specimens were sourced from men who have sex with men and forwarded from 30 clinics throughout the UK. Results: A total of 1112 specimens were screened for the presence of the 377 bp deletion. An in-house PCR method showed that 1066 were wild-type strains. Forty-six strains failed to generate an amplicon and were therefore untypable. This is consistent with differences in the analytical sensitivity of different NAATs and probably reflective of low C trachomatis DNA load. No nvCT strains were identified. Conclusion: Currently, there is no evidence that nvCT is present in England and Wales. However, screening and prevalence studies are continuing and UK clinicians and microbiologists should remain vigilant for suspicious, negative results.